NURSES’ KNOWLEDGE ABOUT NEEDLE STICK INJURY IN AL-NAJAF AL-ASHRAF PEDIATRIC HOSPITALS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Background: Needle1stick injury (NSI)1is a no intentional penetration1of the skin by a needle. Several1studies revealed that nurses1among all other health care workers1are most predominantly1affected primarily due to the nature1of their job. Objectives: The1aims of the study are to assess nurses’ knowledge about needle stick injury and measure the effect of sociodemographic characteristics1of nurses on the knowledge1about needle stick1injury Methods: Cross-sectional1Descriptive study design carried1out in 3 Hospitals; the study sample1is 100 nurses selected by convenience1sample. the data collected from the1sample by self-report1questionnaire. Results: among1of 100 nurses (57%) of sample at1age (26-30) years, (55%) of sample1are females, (46%) of them were institute1graduated, (62%) of them had1more than 10 years of service. (82%)1of sample has high level of1knowledge. The sample1age, education, and years1of service have significant1effect on the level of knowledge Conclusion: nurses have good knowledge1about1NSI. It is necessary to follow1up the nursing staff and improve1their practice about infection control1and standard precaution